Peningkatan Daya Saing UMKM Ramah Lingkungan melalui Pelatihan Kolaborasi Lokal Batusari - Ghanistyana, Lathifa Prima; Khaeriah, Ade Siti (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to explore the strengthening of MSMEs that have a positive impact on the environment in Batusari Village through collaborative training focused on sustainable economic development. In this context, strengthening MSMEs involves local entrepreneurs, village governments, and local communities, with the aim of increasing understanding and capabilities in running businesses that are oriented towards environmental sustainability. The training programme covers increasing awareness of environmentally friendly technology, sustainable business management plans, and the importance of cooperation in local economic development. For the research approach, a qualitative method with a case study design was used in Batusari Village, as this area has great potential in the SME sector that needs to be strengthened with environmentally friendly principles. The research results indicate that this training is effective in improving the management and technical skills of SME actors, as well as strengthening the relationship between business actors and the village government. These findings provide an important perspective for the development of more effective SME empowerment policies in other places, as well as encouraging the implementation of similar programmes that can support sustainable economic development in local communities.